2022
DOI: 10.4103/jomfp.jomfp_446_21
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression and evaluation of cyclin D1 and minichromosome maintenance 2 in oral squamous cell carcinoma and verrucous carcinoma

Abstract: Background: The study of cell proliferation is important for assessing the tumor behavior, prognosis and patient survival of oral carcinomas. As literature search did not reveal sufficient studies of immunohistochemical expression of cyclin D1 and minichromosome maintenance 2 (MCM2) in oral squamous cell carcinoma (OSCC) and verrucous carcinoma (VC), the present study was undertaken. Materials and Methods: The study group included 20 cases of histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The p-value for the association with the tumor grade was 0.157, which was statistically insignificant. These findings are consistent with the findings of Dhingra et al [ 14 ] and Menaka et al [ 13 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The p-value for the association with the tumor grade was 0.157, which was statistically insignificant. These findings are consistent with the findings of Dhingra et al [ 14 ] and Menaka et al [ 13 ].…”
Section: Discussionsupporting
confidence: 94%
“…In a study conducted by Siril et al [ 12 ], 46.5% of tumors showed moderate positivity and 26.19% of tumors showed strong positivity, which is in accordance with the present study. Additionally, a study conducted by Menaka et al [ 13 ] showed a maximum number of cases with strong immunoexpression for cyclin D1, i.e., 40% of the entire cases. The study conducted by Dhingra et al [ 14 ] also demonstrated maximum cases with moderate and strong overexpression, i.e., 27 out of 45 cases.…”
Section: Discussionmentioning
confidence: 99%
“…52 Most investigated markers in carcinogenesis of oral verrucous carcinoma are p53 53,54 , Ki-67 53,55,56 , cyclin-B1 56,57 and cyclin-D1. 58 Except for Ki-67, their expression levels were significantly higher in conventional oral SCC than in oral verrucous carcinoma. Tumour suppression markers p21 and p27 may not be of much diagnostic use in distinguishing oral verrucous carcinoma from oral verrucous hyperplasia 59 and oral SCC.…”
Section: Molecular Biomarkersmentioning
confidence: 93%